Emerging practices in onboarding programs for PAs and NPs. Issue 3 (March 2020) - Morgan, Perri; Sanchez, Mara; Anglin, Lorraine; Rana, Rachel; Butterfield, Rita; Everett, Christine M.
ABSTRACT: Objective: To describe administrative factors that should be considered when designing an onboarding program for physician assistants (PAs) and NPs. Methods: Interview study of 13 administrators of onboarding programs. Interviews were transcribed and analyzed for themes by a team of researchers, with feedback from interviewees. Results: Five administrative themes are summarized: goals of onboarding, critical organization factors, organizational fit, designing the program, and costs of onboarding. Conclusions: Careful planning and administration are essential to the success of onboarding programs. Although onboarding programs must be designed with unique institutional needs in mind, the considerations identified by our project might serve as a useful guide to PA and NP employers in the process of creating an onboarding program.